Death escape: A case study of merging ubiquitous activities into a hardcore computer game - Yasothorn, Prawit; Chueprasert, Tachasit; Towongpaichayont, Witchaya (My University, 2018)
Ubiquitous games can be designed in several settings. This paper presents a case study of designing and developing Death Escape, a role-playing survival ubiquitous game, which is intended to transform user's daily-life activities to in-game player's stats in the con-cept of 'avatar grows as the user grows'. This game is expected to blend the game mechanics with user's behaviours seamlessly. The game collects data from built-in inertia sensors in mobile phones (accelerometer and gyroscope) and GPS, utilises human medical data to transform the collected data into in-game meanings realis-tically, and presents those in-game values to motivate the user to maintain healthy behaviours. This paper describes those methods of data collections and transformations as well as additional findings during the process of design and development. This can set an example for those who are developing ubiquitous games which are blended with the user's lifestyle.
Keywords: Human computer interaction; Mixed reality; Mobile and wireless sensor; Pervasive game; Ubiquitous game